2021
DOI: 10.3390/app112210882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Temperature on the Depletion of Eugenol in Sea Bass under the Simulated Settings in Handling and Transport

Abstract: The edible safety of eugenol-treated fish is one of the concerns limiting the anesthetic applied in the aquaculture industry. The depletion of eugenol was investigated at different water temperatures under the simulated settings of sea bass handling and transport. Sea bass was exposed to eugenol at a concentration of 60 mg/L for 3 min, then immediately transferred to clean water to be purged for 24 h and sampled at different time intervals. The left fish were re-exposed to eugenol in a repeat of the first expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…While further pharmacokinetics studies will be required to clarify these discrepancies, this could raise issues regarding the use of monoterpenes in fish that may be used for food or released into public waterways as a washout period may be required. In this context, while data on withdrawal periods of monoterpene anaesthetics in fish is limited, studies have managed to quantify monoterpenes in tissues of aquatic species up to 12 h post‐anaesthesia after which the levels were reduced to negligible (Erbice Bianchini et al, 2020; Ke et al, 2021; Tang et al, 2022), therefore not surpassing the safety thresholds that may endanger human health (Sartori Tamburlin et al, 2021; Wojtunik‐Kulesza, 2022). As such, different countries have officially licensed eugenol as an aquatic anaesthetic with no withdrawal time (MCC (Medicines Control Council, South Africa), 2004; MPI (Ministry for Primary Industries of New Zealand), 2022) or with a withdrawal period set at 7 days (MAFF (Ministry of Agriculture, Forestry and Fisheries of Japan), 2015) although this compound is not currently FDA‐approved (FDA (Food and Drug Administration, United States of America), 2007) and no information could be found in European agencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While further pharmacokinetics studies will be required to clarify these discrepancies, this could raise issues regarding the use of monoterpenes in fish that may be used for food or released into public waterways as a washout period may be required. In this context, while data on withdrawal periods of monoterpene anaesthetics in fish is limited, studies have managed to quantify monoterpenes in tissues of aquatic species up to 12 h post‐anaesthesia after which the levels were reduced to negligible (Erbice Bianchini et al, 2020; Ke et al, 2021; Tang et al, 2022), therefore not surpassing the safety thresholds that may endanger human health (Sartori Tamburlin et al, 2021; Wojtunik‐Kulesza, 2022). As such, different countries have officially licensed eugenol as an aquatic anaesthetic with no withdrawal time (MCC (Medicines Control Council, South Africa), 2004; MPI (Ministry for Primary Industries of New Zealand), 2022) or with a withdrawal period set at 7 days (MAFF (Ministry of Agriculture, Forestry and Fisheries of Japan), 2015) although this compound is not currently FDA‐approved (FDA (Food and Drug Administration, United States of America), 2007) and no information could be found in European agencies.…”
Section: Discussionmentioning
confidence: 99%
“…quantify monoterpenes in tissues of aquatic species up to 12 h postanaesthesia after which the levels were reduced to negligible (ErbiceBianchini et al, 2020;Ke et al, 2021;Tang et al, 2022), therefore notF I G U R E 2 (a)Evaluation of risk of bias of the included studies by SYRCLE's tool assessing 10 different domains. Contour-enhanced funnel plot analysis of induction (b) and recovery (c) time.…”
mentioning
confidence: 99%
“…In addition, water temperature also plays an important role in the depletion of eugenol. According to the report ( 35 ), the t 1/2 of eugenol in sea bass at a water temperature of 20°C was 0.29 h, while the t 1/2 was 4.5 h at 13°C, indicating that we can increase the temperature to accelerate the depletion of eugenol in fish and reduce residue exposure. However, the withdrawal period is related to the water temperature and the type of drug, thus, it may not change much.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a suitable anesthetic because of its high efficacy, low price, lack of withdrawal period, and lack of negative effects for fish and humans [ 28 , 29 ]. Eugenol has been officially approved as an anesthetic for food fish in many countries, including Japan, New Zealand, and some southeast Asian countries [ 30 ]. Previous studies have reported that eugenol significantly reduces transportation stress in Rhamdia quelen and Lophiosilurus alexandri [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%